Effects of androgenic gland ablation on growth, sexual characters and spermatogenesis of the white shrimp, Litopenaeus vannamei (Decapoda: Penaeidae) males - Alfaro-Montoya, Jorge (2015)
This research was implemented to study the effects of androgenic gland ablation in the white shrimp Litopenaeus vannamei to explore sex reversal potential as an alternative technology for monosex female mariculture based on the sex dimorphic growth of this species. The surgical procedure was applied to male postlarvae (PL) at different ages, after external sex differentiation, as well as in sex undifferentiated PL. Andrectomized males regenerated normal appendices including pereiopods and pleopods; however, body growth and relative size of regenerated petasmas and appendices masculinae were statistically inferior (P ˂ 0.05) to control males. Spermatogenesis in andrectomized males was active, but a phenomenon of degradation of spermatids and reproductive tissues was detected. No sex reversal was accomplished regardless of PL age from sex undifferentiated stages (PL38) to sex differentiated stages (˃PL55). The complete regeneration of sexual characters in andrectomized L. vannamei (Dendrobranchiata) is different from previous reports from Decapoda.